Self-as-a-model interventions situated within an applied model for the use of observation - Ste-Marie, D. M. (Movement & Sport Sciences - Science & Motricité, 2013)
Using the self as a model can occur under two conditions; one in which the person observes their current performance, often as a video replay (self-observation), and another in which video editing is done to only show the learner their most successful past performance or even a performance level not yet achieved (self-modeling conditions). In this paper, I present my research on these two self-as-a-model interventions in the context of a recently developed applied model for the use of observation (Ste-Marie et al., 2012). As such, the literature pertaining to the development of that applied model, and the applied model itself are first presented, followed by current research on the topic of self-observation and self-modeling interventions. Future research directions are also provided.